Factores conformantes del riesgo percibido en los trabajadores de la construcción - Rodríguez-Garzón, Ignacion (2015)
This article is an exploratory study of perceived risk in the construction sector. We used a sample of 514 workers in Spain, Peru and Nicaragua. The method used was the psychometric paradigm and, under its assumptions we have studied nine factors or qualitative attributes of risk. The main statistical analysis was carried out using a classification tree. As a result is obtained that four of the nine attributes studied predict significantly the perceived risk of the sample. The attribute on the delay of the consequences has been the most important predictor in the model, followed by the attribute that explores the potential catastrophic risk and the attribute that explores the serious consequences. Finally the attribute related to the personal vulnerability has emerged. The implications of the results are exposed.